Evaluation of the Activity of Drugs Containing Human Cell Lines: Promising Approaches and Requirements of Regulatory Bodies - A. A. Chaplenko; E. V. Melnikova; O. A. Rachinskaya; Yu. V. Olefir (Антибиотики и Химиотерапия)
This article analyzes the latest requirements of the US and European regulatory authorities for the assessment of the activity of preparations containing human cell lines (biomedical cell product analogues); it gives a review of methods and approaches to the assessment of activity used by manufacturers at different stages of clinical studies and for already registered preparations for cell therapy. Based on the presented data, the basic principles and criteria for the selection of various methods for assessing activity, as well as the interpretation of the results obtained, are formulated. The information presented in the article can be useful both to the manufacturers of biomedical cellular products in the Russian Federation, and to the representatives of regulatory bodies in the process of quality examination.